Living Islam as a Transformative Philosophy: A Systematic Analysis and Integrative Multilevel Conceptual Model - Ali Murfi; Ahmad Syafii; Gatot Prasetyo (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Living Islam scholarship has expanded across Islamic studies, anthropology, education, bioethics, socio-ecological ethics, and digital governance, yet its findings remain fragmented between normative renewal and thick descriptions of everyday practice. This systematic analysis synthesizes how Islam is mobilized as a transformative ethical-philosophical framework under contemporary pressures and develops an integrative multilevel model linking interpretation to public outcomes. Using a protocol-guided search across Scopus, Web of Science, and targeted hand-searching, 764 records were identified; 23 duplicates were removed; 741 titles and abstracts were screened; and 57 full texts were included for content analysis. Coding captured issue domains, philosophical foundations, evidence types, levels of analysis, and recurring mechanisms of change. The corpus clusters into six thematic streams: normative foundations and interpretive renewal; lived Islam, epistemology, and methodology; education and institutional mediation; socio-ecological ethics and sustainability; bioethics and health professions; and human rights, pluralism, governance, and digital/AI ethics. Four gaps emerge: conceptual inflation, discontinuities in the mechanisms linking micro-level practices to policy-level change, limited evaluative designs, and recurring authority contestation and politicization. The resulting model traces ethical transformation from normative reinterpretation to ethical internalization, collective enactment, institutional mediation, policy translation and public governance, and observable outcomes across micro, community, institutional, policy, and global-digital levels. The model offers testable propositions for multiple-case studies across sites, participatory action research, policy evaluation, and mixed-methods validation.